Pengembangan Modul Sport Science Bulu Tangkis Berbasis Android dalam Meningkatkan Prestasi Atlet - Hidayat, Taufiq; Fauqi, Amal; Oktavianis, Ervin; Ramadhan, Rizky (Jurnal Porkes, 2024)
The purpose of this study was to develop an android-based badminton sports science module product in improving athlete performance. Where packaged in the android application in the form of badminton sports science teaching modules in the form of techniques, physical, mental and psychological conditions of athletes. This research is (Research & Development) which refers to the 4-D (Four-D) device development model. The research subjects were 25 badminton athletes. With a research procedure of 4 stages / steps of the define stage (defining), design stage (designing), development stage (developing), dissemination stage (dissemination). The assessment of the experts themselves, namely from sports science experts, obtained an average score of 80 with a very good category. Then the results of badminton experts obtained an average score of 80 with a very good category. Then the media expert obtained an average score of 80 also in the very good category. There are no revisions from the three experts at all and according to the experts the product is very good. The overall result of the expert revision in the large-scale trial was an average score of 29 with a very good category and worth using for badminton athletes of the Bima Regency Provincial Sports Week (Porprov).